2018
DOI: 10.3390/biom8040181
|View full text |Cite
|
Sign up to set email alerts
|

Dual Specificity Phosphatase 6 Protects Neural Stem Cells from β-Amyloid-Induced Cytotoxicity through ERK1/2 Inactivation

Abstract: Alzheimer’s disease (AD) is a devastating neurodegenerative disease with limited treatment options and no cure. Beta-amyloid (Aβ) is a hallmark of AD that has potent neurotoxicity in neural stem cells (NSCs). Dual specificity phosphatase 6 (DUSP6) is a member of the mitogen-activated protein kinases (MAPKs), which is involved in regulating various physiological and pathological processes. Whether DUSP6 has a protective effect on Aβ-induced NSC injury remains to be explored. C17.2 neural stem cells were transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…After exposure to stress conditions, such as hypoxia, inflammation, and irradiation, ER stress is activated, evidenced by the accumulation of unfolded/misfolded proteins, cytoplasmic calcium overload, and ROS outburst (Kim et al 2018;Yang et al 2019). At the molecular level, there are three signaling branches of the ER stress pathway, and they are transcription factor-6 (ATF-6), inositol requiring enzyme 1 (IRE1), and PERK (Liao et al 2018;Shah et al 2019). In the present study, we found that PAMPK was significantly increased in response to HR injury and was inhibited by melatonin.…”
Section: Discussionmentioning
confidence: 99%
“…After exposure to stress conditions, such as hypoxia, inflammation, and irradiation, ER stress is activated, evidenced by the accumulation of unfolded/misfolded proteins, cytoplasmic calcium overload, and ROS outburst (Kim et al 2018;Yang et al 2019). At the molecular level, there are three signaling branches of the ER stress pathway, and they are transcription factor-6 (ATF-6), inositol requiring enzyme 1 (IRE1), and PERK (Liao et al 2018;Shah et al 2019). In the present study, we found that PAMPK was significantly increased in response to HR injury and was inhibited by melatonin.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of curcumin and H 2 O 2 on HUVECs viability were detected by the CCK-8 assay. In brief, cells were cultured on a 96-well plate at a density of 1 × 10 4 per well for 24 h and then administrated with curcumin (0 μ M, 10 μ M, 20 μ M, 30 μ M, 40 μ M, and 50 μ M) for 12 h or with H 2 O 2 (0 μ M, 25 μ M, 50 μ M, 75 μ M, 100 μ M) for another 12 h. Then, the HUVECs were incubated at 37°C for 2 h. Thereafter, a multifunctional microplate reader (SpectraMax M5, Sunnyvale, CA, USA) was adopted to read the absorbance values at 450 nm [16].…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, when miR-125b is overexpressed in hippocampal neurons or directly injected into a mouse hippocampus, it reproduces several hallmarks of AD, such as tau hyperphosphorylation, sustained ERK activation, and DUSP6 decrease [101]. The potential neuroprotective role of DUSP6 in AD is suggested by the results obtained in the C17.2 neural stem cell line, in which DUSP6 overexpression protects against amyloid peptide fragment (Ab 31–35) toxicity and restores normal ERK signaling [102].…”
Section: Dusp In Brain Diseasesmentioning
confidence: 99%